$$3 + (2-4)^2-\frac{6}{3} = $$

Incorrect.
[[snippet]]
You may have gotten this answer if you forgot that the result of squaring a negative number is a positive number.

Incorrect.
[[snippet]]
You may have gotten this answer if you tried to apply the exponent before evaluating what was inside the parentheses.

Correct.
[[snippet]]
> $$3 + ( 2-4)^{2}-\frac{6}{3}$$
> $$= 3 + ( -2)^{2}-\frac{6}{3}$$
> $$= 3 + 4-\frac{6}{3}$$
> $$= 3 + 4-2$$
> $$= 7-2$$
> $$= 5$$

Incorrect.
[[snippet]]
Carefully check your calculations.

Incorrect.
[[snippet]]
Carefully check your work.

-11

-3

3

5

14